Agen Biologis Bioremediasi Logam Berat (Heavy Metal Bioremediation Biologycal Agents) - Bima Syifa Aznur; Siti Khoirun Nisa; Wahyu Adi Septriono (Fakultas Perikanan dan Ilmu Kelautan, 2022)
Environmental pollution from hazardous waste materials, organic pollutants and heavy metals has had a negative impact on natural ecosystems to the detriment of humans. These pollutants arise from anthropogenic sources as well as natural disasters such as hurricanes and volcanic eruptions. Toxic metals can accumulate in agricultural land and enter the food chain, thus becoming a major threat to food security. Conventional and physical methods are expensive and ineffective in areas of low metal toxicity. Therefore, bioremediation is an environmentally friendly and efficient method of reclamation of heavy metal contaminated environments by utilizing biological mechanisms inherent in bacteria, fungi, algae and plants to eradicate harmful contaminants. This review discusses the elimination of heavy metal pollution carried out by bacteria, fungi, algae & plants through extracellular and intracellular mechanisms. Heavy metal bioremediation activities are not only focused on economic aspects, but must be integrated, efficient and sustainable.